Efeito de uma sessão de exercício intervalado de alta intensidade e exercício contínuo de moderada intensidade no perfil imunológico e inflamatório de homens com obesidade - Souza, Daniel Costa de (2017)
Introduction: The excess of body fat is associated with chronic low-grade inflammation and high rates of infectious disease. Emerging evidences indicate that high intensity interval exercise (HIIE) is a time-efficient approach to promote health in obese population. However, little is known about the influence of HIIE on pro and anti-inflammatory cytokine balance in obesity. Purpose: Our purpose was to compare the acute effects of HIIE and moderate-intensity continuous exercise (MICE) on cytokine levels, include interferon-y (INF-y), interleukin 4 and 6 (IL-4) (IL-6) levels and INF-y/IL-4 ratio in obese males. Methods: Ten obese males (BMI>30 kg/m²) were submitted into two experimental sessions with a week interval in a randomized order: 1) HIIE: 10 x 60 s at 90% of HRmáx interspersed by active recovery; 2) MICE: 20 min at 70% of HRmax;. Cytokines was analyzed before, immediately after and 60 min after-exercise. Data was presented in mean ± SD. ANOVA 2-way with repeated measures and post hoc Bonferoni was used to assess differences between moments and exercise conditions. Statistical significance was accepted at a p value of ≤ 0.05. Results: The HIIE results in decreased INF-Y levels immediately after-exercise (41,09 ± 4,74; P=0,032) and 60 min after-exercise (43,45 ± 3,72) (P=0,003) compared with before-exercise (46,64 ± 4,15), while an significant elevation in IL-4 levels was observed immediately after-exercise (36,47 ± 3,5) (P=0,007). The MICE results in increase of INF-Y levels after exercise (P=0,025) and 60 min post-exercise (P=0,004). Both exercise conditions results in increase of IL-6 levels after exercise (P<0.05). The INF-Y/IL-4 ratio decreases immediately after (P=0,002) and 60 min after-exercise (P=0,005) only for HIIE. Conclusion: HIIE induces imbalance in INF-Y/IL-4 ratio 60 min after exercise following an anti-inflammatory pattern. For other hand, MICE did not promote imbalance in INF-Y/IL-4 to 60 min after exercise in obese males.